First report of an egg nursery for the Critically Endangered flapper skate Dipturus intermedius (Rajiformes: Rajidae). Issue 10 (11th July 2022) - Dodd, Jane; Baxter, John M.; Donnan, David W.; James, Benjamin D.; Lavender, Edward; McSorley, Claire A.; Mogg, Andrew O.M.; Thorburn, James A.
Abstract: This study provides the first report of an egg nursery for the Critically Endangered flapper skate Dipturus intermedius and a description of the habitat, thus contributing towards our understanding of essential habitats for the species. In total, 1, 395 flapper skate egg cases were recorded (accounting for overlapping surveys) in two egg case collection dives ( n = 67 egg cases), one photogrammetry dive ( n = 10 egg cases), 509 drop‐down video (DDV) camera drifts ( n = 510 egg cases) and 18 remote operated vehicle (ROV) flights ( n = 1, 031 egg cases), carried out in the Inner Sound on the west coast of Scotland from 2018 to 2021. All of the egg cases were found on a shallow bedrock plateau between the Isle of Scalpay and a deep (>100 m) water channel between the Isle of Longay and the Crowlin Islands. Egg cases were observed on a cobble/boulder reef between 25 and 58 m depth, with a modelled annual temperature range of 9–12 °C, modelled current speeds up to 0.2 m −1, a rugosity index of 1.7 and low levels of sedimentation. Flapper skate egg cases are large and the incubation period is protracted (18 months), making them potentially vulnerable to anthropogenic disturbance. A description of the habitat where egg cases were observed in this study will help inform the search for egg nurseries for this Critically Endangered species elsewhere. Targeted DDV, ROV and scuba diving surveys will support this search in areas where suitable bathymetric and hydrodynamic conditions are identified. Safeguarding egg nurseries is essential for successful conservation. Protection should involve the designation of egg nurseries as Marine Protected Areas where activities that are likely to damage or alter seabed habitats are managed.